Indicadores de capital social para o desenvolvimento rural sustentável em unidades de agricultura familiar na costa oeste paranaense - Serafim Junior, Valdir (2020)
The objective of this study is to identify in the region of the West Coast of Paraná, in the context of family farming, the main characteristics that promote social capital and its contribution to sustainable rural development. A detailed characterization of a sample of family units in this region was carried out, taking into account their characteristics in relation to social ties with the territory, relations with the new rurality, productive interactions, commercialization processes and existing income and signal from the concepts of social capital and its existence, related to the basic dimensions of DRS - Sustainable Rural Development. The sources of information were extracted from the reports of the “Organic Agriculture Project in BP3 - Paraná Basin 3”, work conducted and developed by Biolabore - Cooperative of Labor and Technical Assistance of Paraná, in conjunction with Itaipu Binacional, originated from 535 units of family farming with agroecological potential during the period from 04/2015 to 04/2018, representing the research population. It used a sample of 200 units and from the descriptive statistics the analyzes and interpretations were made. In the characterizations of the family units, the need for reflection on the perspective of successors was found, the pluriactivity in the units was identified and the conviviality and participation in social organizations showed strong links with religious entities, cooperatives and associations, these units have characteristics of the aging process, there is an educational opportunity for the youngest and there was a delay in the older generations. There is no considerable dedication of young labor to agricultural activities, with homogeneity of variances between men and women in terms of age and days spent on property, predominantly, the units are composed of small areas and with low levels of technical assistance, they normally use conventional agricultural practices, as productive specialization the activities of dairy cattle and olericulture were identified, while the main productive networks stand out the activities of dairy cattle, olericulture, beef poultry, fruit, corn and soy, there are several strong marketing networks linked to local markets (fairs and direct sales), institutional markets (government purchases) and conventional markets (dairy and cooperatives). Dairy activity, commodity production and olericulture were identified as the main activities that generate agricultural income, identifying which of these characteristics are forming and enhancing social capital and their relationship with sustainable rural development, finding the Social Capital Index (ICS) ) in these units, demonstrating that the higher the social capital index found in the units, the greater the possibility that reconciliation with the basic dimensions of the DRS is also found, within the environmental, social, economic, cultural, political and ethical context . From the analysis, it can be inferred that there is a need to develop efficient public actions and policies for local development, ensuring the consolidation of sustainable rural development, especially in the aspects that least contributed to the composition of the ICS, such as the concern with succession processes, the low role in functions in the social integration entities, the little political representation through participation in development councils, the lack of technical assistance and an analysis of the possibilities of expanding the units in institutional markets.